Penyuluhan Risiko Bahan Kimia Laundry serta Penerapan Keselamatandan Kesehatan Kerja (K3) di Industri Laundry - Indah Permata Sari; Dian Mardi Safitri; Winnie Septiani; Bambang Cholis Su'udi (Abdimas Universal, 2023)
The laundry industry is one of the industries that is growing rapidly at this time. The development of this industry cannot be separated from the growing need for human clothing. While carrying out their work, laundry workers have a risk of exposure to laundry chemicals. However, most laundry workers do not understand these risks and how to prevent and handle them. This service activity aims to provide counseling to laundry workers regarding the risks of laundry chemicals and the application of occupational safety and health in the laundry industry. Counseling was carried out directly to one of the laundry industries in Tangerang City, involving 14 laundry workers. The material provided includes various types of laundry chemicals, potential hazards, how to prevent them and the need for OSH applications such as the use of PPE in work. The results of the activity evaluation show that this counseling activity has an impact on increasing the knowledge of laundry workers regarding the risks of laundry chemicals and how to prevent and handle them. Evaluation of the usefulness of the activity and the activity presenter gave the result that the presenter conveyed the material clearly so that all laundry workers agreed that this extension activity was very useful.